Nothing As We Need It A Chimera - Cascella, Daniela (punctum books, 2022)
Nothing As We Need It: A Chimera imagines and writes a composite and impure form of criticism that embodies the writing of research as recursive, entangled, and many-voiced. Shaped by encounters with literature not translated in English, by the polyphonies, artifices, and concealments of a bilingual self, and by the sense of speechlessness and haunting when writing of works that cannot be instantly quoted, this book's subtitle derives from the mythological Chimera: a monstrous creature made of three different parts, impossible in theory but real in the imagination and in the reading of the myth. Similarly the book is written in different styles, some of which may seem impossible, monstrous, and disturbing. It manifests critical writing as enmeshment and conversation with its subject matters; favours impurity rather than detachment; embraces exaggeration, repetition, laughter, and self-parody as legitimate forms of knowledge. Yet a chimera also designates the object of a yearning deemed unattainable: this book exists in the space of such yearning, in the tension between words and what exceeds them, their overtones. The critic is exhausted by yearning, rather than the owner of exhaustive knowledge. A Menippean satire for critical writing, Nothing As We Need It sustains its argument for composite and impure writing in its form. It demands ways of reading equally varied, and wildly imaginative. Listening to literature beyond the limits of textual analysis, it dismisses the visual implications of reflection, which assumes detachment and polished surfaces, in favour of an aural method of resonance, allowing enmeshment and interference. This book unsettles language, welcomes uninhibited exaggeration and wordplay, and manifests possibilities for working with citation beyond the boundaries of inverted commas.